Türkiye’de Dijital Gazetecilik: Habertürk Ve Hürriyet Gazeteleri Örneği - Aydoğan, Derya (The Turkish Online Journal of Design, Art and Communication, 2013)
Nowadays digitalization starts to gain power and importance. Thus newspapers which means of communicaton are affected as negatively and positively inevitably. The newspaper was the most important mass communication from past to present but it had to limited facilities about the length of news, diversity of news or number of pictures. This problem was disappeared through the emergence of online newspapers. Online newspapers are more advantageous than traditional newspapers because of they includes like pictures, videos and articles. Online newspapers' another advantage is sharing in social media through they have to comments section, participation of reader and share button also. Their disadvantage is causing information pollution because of they includes lots of data. In this study the important first five news of Habertürk newspaper and Hürriyet newspaper which online and printed are discussed and compared with each others. Shannon-Weaver's Information Theory, Manuel Castells' Network Society theory and Marshall McLuhans' Global Village and The Medium is the Messeage theories are used in this study.
Keywords: Digitalization; Online Newspaper; Traditional Newspaper; News; Dijitalleşme; Online Gazete; Geleneksel Gazete; Haber